In-depth genome-wide characterization of MaNAC25 and MaNAC28 cold-responsive transcription factor binding sites in banana via DAP-Seq - Chunbo Song (Current Plant Biology)
Mapping transcription factor proteins' binding sites across the entire genome in banana is crucial for unveiling their transcriptional regulatory mechanisms and enhancing our understanding of their regulatory networks. Our study showed that DAP-Seq experiments identified MaNAC25 and MaNAC28 numerous binding peaks, mainly in the promoter regions, with strong signals near the transcription start site (TSS). Significantly, the discovery of new binding motifs for MaNAC28 excluding NAC core binding element CGTA/G indicates their potential as novel DNA binding motifs for NAC transcription factors in cold stress response. Moreover, MaNAC25 was found to chiefly influence biological processes and molecular functions, whereas MaNAC28 was more focused on molecular functions. Both MaNAC25 and MaNAC28 extended their regulatory networks by interacting with other transcription factors during cold stress. Therefore, DAP-Seq technology furnishes essential insights and a robust foundation for researching transcriptional regulatory mechanisms among diverse transcription factors and broadening their regulatory networks.